Securing Wireless Sensor Networks, Types of Attacks, and Detection/Prevention Techniques, An Educational Perspective - Tuka Kareem Jebur (Universitas Pendidikan Indonesia (UPI), 2024)
Wireless sensor networks (WSNs) are gaining popularity in a variety of applications, including smart homes, industrial facilities, and environmental monitoring systems. However, using WSNs exposes them to a variety of attacks that might have major effects, such as data loss, privacy breaches, and safety issues. As a result, understanding the sorts of threats and detection/prevention strategies in WSNs is critical to ensuring their security, especially from an educational perspective. We present an overview of the sorts of attacks that can occur in WSNs, including denial of service attacks, spoofing attacks, jamming attacks, physical assaults, and node compromise attacks. We also examine encryption, authentication and authorization procedures, intrusion detection systems, and physical security measures as methods for detecting and blocking attacks in WSNs. We examine the benefits and drawbacks of each strategy and give case studies to show their efficacy. Finally, we propose future research directions, such as the development of more effective intrusion detection systems and the enhancement of physical security measures. We can assure the security and reliability of WSNs in diverse applications by knowing the types of attacks and detection/prevention mechanisms.